Fundamentals of urodynamic practice, based on International Continence Society good urodynamic practices recommendations. (15th August 2018) - Drake, Marcus J.; Doumouchtsis, Stergios K.; Hashim, Hashim; Gammie, Andrew
Abstract : Aims: To review the recommendations on basic urodynamic testing in the International Continence Society (ICS) standardization documents, specifying key recommendations for delivery and interpretation in clinical practice. Methods: Fundamental expectations described in the ICS standards on good urodynamic practices, urodynamic equipment, and terminology for lower urinary tract (LUT) function were identified and summarized. Results: The ICS standard urodynamic protocol includes clinical history, including symptom and bother score(s), examination, 3‐day voiding chart/diary, representative uroflowmetry with post‐void residual, and cystometry with pressure‐flow study (PFS). Liquid filled catheters are connected to pressure transducers at the same vertical pressure as the patient's pubic symphysis, taking atmospheric pressure as the zero value. Urodynamic testing is done to answer specific therapy‐driven questions for treatment selection; provocations are applied to give the best chance of reproducing the problem during the test. Quality of recording is monitored throughout, and remedial steps taken for any technical issues occurring during testing. Labels are applied during the test to document events, such as patient‐reported sensation, provocation tests, and permission to void. After the test, the pressure and flow traces are scrutinized to ensure artefacts do not confound the findings. An ICS standard urodynamic report details the key aspects, reporting clinical observations, technical, and quality issues. Urodynamic services must maintain and calibrate equipment according to manufacturer stipulations. Conclusions: The review provides a succinct summary of practice expectations for a urodynamic unit offering cystometry and pressure flow studies (PFS) to an appropriate standard.